The Principle of Inviolability of Diplomatic Correspondence under the Vienna Convention on Diplomatic Relations (1961): Problems of Implementation - Safina A. N. (Days of Student Science, 2022)
the article describes the legal regime for the protection of the inviolability of official correspondence. The problems of this procedure implementing are analyzed.
Keywords: дипломатическая переписка; неприкосновенность; вализа; допустимость доказательств; diplomatic correspondence; inviolability; diplomatic bag; admissibility of evidence